EVALUASI HASIL PENCUCIAN RAW MATERIAL KAOLIN TERHADAP KEBUTUHAN PRODUKSI UNIT PENGOLAHAN PT ANEKA KAOLINE UTAMA BELITUNG - Mukram Belto Pratama; Irvani Irvani; Mardiah Mardiah (MINERAL, 2021)
PT Aneka Kaoline Utama produces kaoline powder through two processes which are washing are washing unit and processing unit. Washing unit does the separation between tailing and kaoline with the extract as the result. The extract contains water and kaoline, then the water reduction will be processed in processing unit. Based on the information, writer evaluates the extract production in washing unit for fulfilling the needs of processing unit in PT Aneka Kaoline Utama using evaluation method and action research method. The steps are sampling raw material (feed), calculating the sediment pond’s dimention and the volume of full pond, sampling tailing in washing unit’s tools, observing the production’s process, and evaluating the needs off kaoline extract. The result of this research shows that raw material in washing unit were 3,847.4 ton in April, 3,606.2 ton in May, 2,594.9 ton June, and 3,890 in July which showed the amound of extract did not reach the target in processing unit. 69.2% of loose material and 21% loosing kaolin in average caused the recovery value in washing unit just reached 30.8%. Because of loose kaoline’s presence in washing unit, writer suggests the increasing of raw material and working hour as big as 27,056.3 ton per hour with 30.8% washing unit’s recovery so the company can produce 8.34 ton kaoline per hour and 4,000 ton kaoline per month.